Analisis Sitem Pengendalian Intern Kas pada PT Pelabuhan Indonesia I (Persero) Medan - Wasih Latuh Rahmi (Masyarakat Ekonomi Syariah Bogor, 2023)
Cash is referred to as the most liquid property and is a component of current assets which include banknotes / metals and other objects that can be used as a legal and retrievable medium of exchange every time. If the cash inventory is sufficient, the company will operate smoothly, especially in cash expenditure activities which include the purchase of goods and services, and therefore in order for the company to avoid misappropriation, the cash is used as well as possible. Cash is inseparable from receiving and payment activities. The purpose of this study is to describe how the Cash Internal Control System and analyze the Cash Internal Control System in the company of PT. Port of Indonesia I (Persero) Medan. The internal cash control system is a control system that is able to protect the company's cash, and keep away from losses due to intentional or unintentional mistakes. The internal control system is divided into two systems, namely cash receipts and expenditures. In this study, the problem arises because of the sequence number of the evidence that is not printed and does not have a stamp stamp